2018
DOI: 10.1038/s41598-018-24513-w
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Integration Processes in Visual Symmetry with Frequency-Tagged EEG

Abstract: Symmetry is a highly salient feature of the natural world which requires integration of visual features over space. The aim of the current work is to isolate dynamic neural correlates of symmetry-specific integration processes. We measured steady-state visual evoked potentials (SSVEP) as participants viewed symmetric patterns comprised of distinct spatial regions presented at two different frequencies (f1 and f2). We measured intermodulation components, shown to reflect non-linear processing at the neural leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Other SPN work has shown that the extrastriate symmetry network always responds to symmetry in the image, but can sometimes go beyond this and recover symmetry in the object, independent of changes in virtual view angle ( Makin, Rampone, & Bertamini, 2015 ) and despite partial occlusion ( Rampone, Makin, Tatlidil, & Bertamini, 2019 ). Finally, the steady-state visual evoked potential approach can be used to isolate the symmetry response in the odd harmonic frequencies ( Alp, Kohler, Kogo, Wagemans, & Norcia, 2018 ; Kohler et al., 2016 ; Norcia, Candy, Pettet, Vildavski, & Tyler, 2002 ) and the amplitude of this signal also scales with symmetry salience ( Oka, Victor, Conte, & Yanagida, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other SPN work has shown that the extrastriate symmetry network always responds to symmetry in the image, but can sometimes go beyond this and recover symmetry in the object, independent of changes in virtual view angle ( Makin, Rampone, & Bertamini, 2015 ) and despite partial occlusion ( Rampone, Makin, Tatlidil, & Bertamini, 2019 ). Finally, the steady-state visual evoked potential approach can be used to isolate the symmetry response in the odd harmonic frequencies ( Alp, Kohler, Kogo, Wagemans, & Norcia, 2018 ; Kohler et al., 2016 ; Norcia, Candy, Pettet, Vildavski, & Tyler, 2002 ) and the amplitude of this signal also scales with symmetry salience ( Oka, Victor, Conte, & Yanagida, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Boremanse et al (2014) reported that the beat was absent when the two halves of a face stimulus were misaligned or separated. Alp et al (2018) also revealed that conditions without global integration (i.e. scrambled control and rotated control) had smaller beats compared with those using reflection symmetry stimuli.…”
Section: Neural Entrainment Had Only Moderate Effectsmentioning
confidence: 83%
“…IM components were only specific to the holistic processing condition when two halves formed the whole face (Boremanse, Norcia, & Rossion, 2013;Boremanse, Norcia, & Rossion, 2014). IM components have also been shown to represent perceptual binding in binocular and interocular rivalry (Sutoyo & Srinivasan, 2009), in perceiving coherent patterns (Cunningham, Baker, & Peirce, 2017), illusory contours (Alp, Kogo, Van Belle, Wagemans, & Rossion, 2016), and symmetry (Alp, Kohler, Kogo, Wagemans, & Norcia, 2018). Therefore, beat as one of IM components is well-established in vision studies.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent follow‐up study, Alp et al . measured SSVEP as participants viewed symmetric patterns composed of distinct spatial regions presented at two different frequencies ( f 1 and f 2 ).…”
Section: Type Of Symmetry and Regularitymentioning
confidence: 99%